2008
DOI: 10.4314/bahpa.v55i4.32814
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Sole Haemorrhages And Its Correlation With Subclinical And Chronic Laminitis In Dairy Cows

Abstract: Nguhiu-Mwangi, J; Mbithi, P.M.F.; Wabachal, J.K.; Mbuthia, P.G. Date: 2007 Prevalence and risk factors of laminitis were determined in 300 dairy cows from 29 zero-grazed and 3 pasture-grazed dairy farms in Nairobi and the peri-urban districts. Lameness was assessed using a universally recognized locomotion scoring system. Claws were examined and 1-2mm thick layer of the horn of the sole was trimmed-off to further expose underlying lesions. Location of lesions on the under-side of the claws was recorded corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Ignorance and negligence of claw trimming practices in the zero-grazing units that were included in this study have been major cause and an aggravating factor in the progression of claw disorders to chronic stages. This contributes to long-term claw damage and worsens the prognoses (Nguhiu-Mwangi, 2007). It has been shown that trimming of hooves leads to lower locomotion scores and reduced clinical lameness (Manson & Leaver, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ignorance and negligence of claw trimming practices in the zero-grazing units that were included in this study have been major cause and an aggravating factor in the progression of claw disorders to chronic stages. This contributes to long-term claw damage and worsens the prognoses (Nguhiu-Mwangi, 2007). It has been shown that trimming of hooves leads to lower locomotion scores and reduced clinical lameness (Manson & Leaver, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the claws cannot be conclusive without trimming at least the horn of the sole. This is necessitated by the fact that lesions underneath the horn of the claws are not discernible externally until exposed by trimming (Nguhiu-Mwangi, 2007;Nocek, 1997). Such routine examination will help to recognize and manage claw disorders in the early stages before they progress to unmanageable chronic stages in which the claws are irreversibly damaged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These macroscopic deformities are often accompanied by irreversible damage to the internal structure of the claws [6][7][8][9]. Initially, laminitis occurs in a subtle clinically unrecognised state referred to as subclinical laminitis, which can only be discerned through claw trimming as sole and white line haemorrhages [6,10,11]. The haemorrhages are associated with pododermal microvasculature changes that lead to extravasation of serum and blood elements with subsequent staining of the internal layers of the horn next to the corium of the claw and later following horn-growth towards the surface of the sole, becomes visible externally as sole haemorrhages [6,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, laminitis occurs in a subtle clinically unrecognised state referred to as subclinical laminitis, which can only be discerned through claw trimming as sole and white line haemorrhages [6,10,11]. The haemorrhages are associated with pododermal microvasculature changes that lead to extravasation of serum and blood elements with subsequent staining of the internal layers of the horn next to the corium of the claw and later following horn-growth towards the surface of the sole, becomes visible externally as sole haemorrhages [6,11,12]. If claw trimming or keen observation is not done routinely in individual dairy cows, subclinical laminitis advances to chronic phase of laminitis and predisposes to laminitis-related non-infectious claw disorders with likelihood of occurrence of irreversible internal damage in the claws [6,13].…”
Section: Introductionmentioning
confidence: 99%